2005
DOI: 10.1071/rd04102
|View full text |Cite
|
Sign up to set email alerts
|

Understanding cellular disruptions during early embryo development that perturb viability and fetal development

Abstract: An inability to regulate ionic and metabolic homeostasis is related to a reduction in the developmental capacity of the embryo. The early embryo soon after fertilisation and up until compaction appears to have a reduced capacity to regulate its homeostasis. The reduced ability to regulate homeostasis, such as intracellular pH and calcium levels, by the precompaction-stage embryo appears to impact on the ability to regulate mitochondrial function and maintain adequate levels of energy production. This reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(70 citation statements)
references
References 76 publications
4
63
0
3
Order By: Relevance
“…Additionally, a greater understanding of embryonic metabolism may provide new approaches to assessing embryonic viability and screening for inborn errors of metabolism. For example, a recent study reported that higher rates of lactate production in murine embryos cultured in vitro were associated with reduced viability following uterine transfer (36). The size and accessibility of the early mammalian embryo no longer represent such significant impediments to investigating early embryonic metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a greater understanding of embryonic metabolism may provide new approaches to assessing embryonic viability and screening for inborn errors of metabolism. For example, a recent study reported that higher rates of lactate production in murine embryos cultured in vitro were associated with reduced viability following uterine transfer (36). The size and accessibility of the early mammalian embryo no longer represent such significant impediments to investigating early embryonic metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that apoptosis increases when embryos are cultured under suboptimal conditions (19)(20)(21)(22)(23)(24). Increased apoptosis in blastocysts (and consequently fewer healthy inner-cell mass cells) impairs embryonic and fetal development (21,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…This finding may involve altering culture conditions because such changes can positively affect embryo metabolism and gene expression. For example, including amino acids in the culture medium enhances the embryo's ability to implant and develop after transfer (33,34). This effect correlates with the observation that amino acids can reduce the enhanced glycolytic rate that is observed in early To measure the retention of spatial information on a per subject basis, an animal's performance on day 21 was compared with its performance on day 1, and the data are expressed as this ratio minus 1 so that identical performance on day 21 and day 1 results in a value of 0.…”
Section: Discussionmentioning
confidence: 99%